2022
DOI: 10.3390/s22145069
|View full text |Cite
|
Sign up to set email alerts
|

Rendering Immersive Haptic Force Feedback via Neuromuscular Electrical Stimulation

Abstract: Haptic feedback is the sensory modality to enhance the so-called “immersion”, meant as the extent to which senses are engaged by the mediated environment during virtual reality applications. However, it can be challenging to meet this requirement using conventional robotic design approaches that rely on rigid mechanical systems with limited workspace and bandwidth. An alternative solution can be seen in the adoption of lightweight wearable systems equipped with Neuromuscular Electrical Stimulation (NMES): in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…The use of e-textile solutions with greater comfort and reduced conscious athlete awareness may somewhat remove the constraint on the number and position of sensors. Any developed tools for the estimation of tissue-specific internal biomechanical training loads may facilitate the prescription and monitoring of specific loads, as well as the ranking of exercises in terms of specific tissue loading [ 90 , 91 ] or the provision of haptic [ 92 , 93 ] or audio [ 94 , 95 ] biofeedback.…”
Section: Technology and Sensing In Sports And Fitnessmentioning
confidence: 99%
“…The use of e-textile solutions with greater comfort and reduced conscious athlete awareness may somewhat remove the constraint on the number and position of sensors. Any developed tools for the estimation of tissue-specific internal biomechanical training loads may facilitate the prescription and monitoring of specific loads, as well as the ranking of exercises in terms of specific tissue loading [ 90 , 91 ] or the provision of haptic [ 92 , 93 ] or audio [ 94 , 95 ] biofeedback.…”
Section: Technology and Sensing In Sports And Fitnessmentioning
confidence: 99%
“…Their findings indicated that the biceps brachii and triceps brachii's actuation had the most significant impact on weight perception. Lastly, Galofaro et al [34] developed an experimental setup to enhance user interactions with virtual reality objects. Specifically, their focus was on users holding and lifting a virtual cube, with the key aspect being the ability to perceive the cube's weight as if it were a real object.…”
Section: Kinesthetic Feedback Applicationsmentioning
confidence: 99%
“…Therefore, this study aimed to investigate the potential impact of food color and temperature on the psychological changes of anorexia nervosa patients through a muscle stimulation experimental approach [16]. A specific experimental setup was employed, featuring a lightweight wearable device equipped with muscle stimulation.…”
Section: Introductionmentioning
confidence: 99%